Consumers Perception of Online Shopping Intention - Wiryanta Muljono; Sri Setiyawati (Department of Management, Faculty of Economics and Business, Brawijaya University, 2021)
Service quality includes shipping has been considered a critical factor that affects continuance intention consumers in online shopping. This study investigate whether attitude acts as a moderator between service quality and shipping with regard to continuance intention in online shopping. This study was conducted using a quantitative approach by distributing questionnaires to online shopping consumers. Utilizing SEM with AMOS 22 by sampling 400 respondents. These empirical findings provide one, among several others, insight (recommendation) to startup in developing service quality and shipping because online shoppers are more concerned with their goods being immediately received thus weathering the competition from other startups. Study concluded that the employed service features produced a significant influence on the continuance intention of online shopping. The Startup company knew who its consumers can differentiate products and services which are offered by the company and others. Righteously startup company has also a strong commitment to ensuring that it will deliver goods on time to consumers. The limitation of the present study originates from the research scope which revolves around consumer's perception of service quality included shipping on a startup company.